Artisanal and farmer bread making practices differently shape fungal species community composition in French sourdoughs - Michel, Elisa; Masson, Estelle; Bubbendorf, Sandrine; Lapicque, Léocadie; Nidelet, Thibault; Segond, Diego; Guézenec, Stéphane; Marlin, Thérèse; Devillers, Hugo; Rué, Olivier; Onno, Bernard; Legrand, Judith; et al. (Peer Community Journal)
Preserving microbial diversity in food systems is one of the many challenges to be met to achieve food security and quality. Although industrialization led to the selection and spread of specific fermenting microbial strains, there are still ongoing artisanal processes that may allow the conservation of a wider species diversity and genetic diversity. We examined whether the diversity of artisanal practices could lead to an increased level in fungal species diversity for bread making. We used an interdisciplinary participatory research approach including bakers, psycho-sociologists and microbiologists to analyze French bread making practices and describe fungal communities in naturally fermented sourdough of 27 bakers and 12 farmer bakers. Bread making practices were classified in two groups: the farmer-like practice group and the artisanal-like practice group. The well-known bakery yeast, Saccharomyces cerevisiae, was dominant (i.e. with a relative abundance over 50%) in only 24% of sourdoughs while other yeast species, belonging to the Kazachstania genus, were dominant in 54% of sourdoughs. Bread making practices were found to drive the distribution of fungal species across sourdoughs. The most striking bread making practice effect was the occurrence of Kazachstania humilis in sourdoughs made with artisanal-like practices and the occurrence of Kazachstania bulderi in sourdoughs made with farmer-like practices. Phenotypic divergences between sourdough and non-sourdough strains were found for K. humilis but not for K. bulderi. Overall, our results showed that preserving bread making practice diversity allows the preservation of a higher species and phenotypic diversity in microbial communities.